Determination of the adsorption energy of some volatile solvents on the surface of a mesoporous carbon adsorbent by gas-chromatography - Snauko, Marian (Array, 2008)
Summary: Retention times of 21 volatile solvents were determined on a mesoporous carbon adsorbent stationary phase by gas chromatography at various column temperatures and the energy of adsorption was calculated from the dependence of the retention time on the column temperature. Energies of adsorption showed high variations proving that the carbon stationary phase is suitable for separation of this class of analytes. Quantitative structure-retention computations demonstrated that the strength of adsorption significantly depends on the molecular volume, indicating the dominant role of sterical correspondence in the adsorption